Introduction - Elisabeth Camp (Baltic International Yearbook of Cognition, Logic and Communication, 2007)
Here, I offer a rapid overview of the theory of metaphor, in order to situate the contributions to this volume in relation to one another and within the field more generally.
Keywords: philosophy; linguistic